Spotlight on available optical properties and models of nanofluids: A review - Hossain, M.S.; Saidur, Rahman; Sabri, Mohd Faizul Mohd; Said, Z.; Hassani, S. (Elsevier, 2015)
Optical characteristics besides unique thermo-physical properties of nanoparticles have encouraged researchers to use nanofluids in solar energy collectors or reservoirs as electromagnetic wave absorbing media. Recently, different analyses and approaches have been proposed by researchers. However, the appropriate electro-magnetic phenomenon of nanofluids is not established till date because of the complex dependence between nanoparticles and base fluids. In this work, optical properties of nanofluids are discussed on the basis of published data; mostly used models are presented along with their limitations and applications. (C) 2014 Elsevier Ltd. All rights reserved.